Effect of concentration of Cd on structural and optical properties of ZnO:Cd thin films prepared by sol-gel method - Khudiar, Ausama I. (IJRDO-Journal of Applied Science, 2016)
Cadmium doped zinc oxide polycrystalline thin films were prepared by sol-gel process. The sol was prepared from zinc acetate dehydrate and cadmium acetate was used to it. Methoxyethanol and monoethanolamine were used as solvent and stabilizer, respectively. The quantity of cadmium in the sol was 0, 1, 5 and 10 at % Cd. Structural investigation including microstructure was carried out by X-ray diffraction (XRD) analysis. The films give a hexagonal wurtzite structure with diffraction peaks at (100), (002) and (101). It is found that the particle size of the films change with Cd doping. Optical properties of the thin films were determined by using UV-VIS-NIR spectrometer. It was found that the band gap of the thin films decreased from 3.16 eV to 2.6 eV as the concentration of Cd was increased. Such films can be applied on silicon solar cells as the changes in the band gap are acceptable as a requirement for good anti-reflecting coating element.